(untitled) (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2024)
This literature review examines China’s rise as an emerging international hegemon and its impact on the transformation of the global order. Grounded in Organski’s power transition theory, the study explores this framework’s theoretical principles and empirical evidence while distinguishing it from classical realism. The review outlines the phases of power transition—potential power, transitional growth, and power maturity—and applies these phases to China’s historical trajectory from an agrarian economy to an industrialized global power. Special emphasis is placed on pivotal milestones, including Mao Zedong’s economic strategies, Deng Xiaoping’s market reforms, and Xi Jinping’s assertive policies such as the Belt and Road Initiative (BRI). Through the lens of power transition theory, the article highlights China’s strategic efforts to challenge Western dominance, particularly the United States (US), and reshape the international order. This study raises critical questions about the future of global leadership and stability amidst the shifting power dynamics between a declining US and a rising China.